Electronic quantum coherence in glycine molecules probed with ultrashort x-ray pulses in real time - Schwickert, David; Ruberti, Marco; Kolorenč, Přemysl; Usenko, Sergey; Przystawik, Andreas; Baev, Karolin; Baev, Ivan; Braune, Markus; Bocklage, Lars; Czwalinna, Marie Kristin; Deinert, Sascha; Düsterer, Stefan; et al. (Science advances, 2022)
Here, we use x-rays to create and probe quantum coherence in the photoionized amino acid glycine. The outgoing photoelectron leaves behind the cation in a coherent superposition of quantum mechanical eigenstates. Delayed x-ray pulses track the induced coherence through resonant x-ray absorption that induces Auger decay and by photoelectron emission from sequential double photoionization. Sinusoidal temporal modulation of the detected signal at early times (0 to 25 fs) is observed in both measurements. Advanced ab initio many-electron simulations allow us to explain the first 25 fs of the detected coherent quantum evolution in terms of the electronic coherence. In the kinematically complete x-ray absorption measurement, we monitor its dynamics for a period of 175 fs and observe an evolving modulation that may implicate the coupling of electronic to vibronic coherence at longer time scales. Our experiment provides a direct support for the existence of long-lived electronic coherence in photoionized biomolecules.